Kategoria bohatera absurdalnego w Kamieniu na kamieniu Wiesława Myśliwskiego oraz Sońce Ignacego Karpowicza - Andrzej Jamiołkowski (Studia Slavica)
The article is an attempt to find elements of the concept of the absurd man presented by Albert Camus in the essay The Myth of Sisyphus in selected texts of polish rural prose. The heroes of Kamień na Kamieniu and Sońka, in a way similar to the mythical Sisyphus, whom Camus presents as a model of a person overcoming the absurdity of existence, deal with the nonsense of existence. The attitudes presented by the characters presented are driven by quiet, inconspicuous heroism, the symptom of which is the disagreement with the lack of a deeper meaning that accompanies their existence.